Entre o espelho e o reflexo: cultura material, patrimônio e memória através da leitura da coleção do Sr. Barrô pertencente ao Museu de Arqueologia e História de Maués-AM - Oliveira, Murana Arenillas (2018)
ABSTRACT Collections of objects gathered by family units are common in the interior of the state of Amazonas. Here, they are established as “home museums”—small, informally-created museums in domestic settings. Considering that the collections are formed through the occurrence of archeological findings, it is necessary to discuss the concepts that permeate their conception, such as archeological material culture, collections, heritage, and museums. Therefore, this work consists of understanding the study of social relations between the “collection of Mr. Barrô” and voluntary acts by social agents involved in this relation. Through the Maués Museum of Archeology and History, known as the “Collection of Mr. Barrô,” we will then reflect on informal initiatives to create “home museums” in the interior of the state of Amazonas—specifically in the municipality of Maués, where this collection is located. In view of this, we raise the following question: could “home museums” become alternatives for safeguarding archeological artifacts found abundantly in the Amazon? As such, we substantiate this research with narratives from the very social agents who contribute, through initiatives like these, to the context and history of the city of Maués. Keywords: Home Museums, Barrô collection, Archeology-Amazonas, Maués- AM.